(untitled) (Research, Society and Development, 2021)
The objective of this manuscript is to analyze aspects of the Brazilian legal system related to advance directives of will and discuss the need for a specific regulatory law. This is a study carried out using the deductive method, based on bibliographical research and on the study of fundamental and constitutional principles, as well as on the resolutions of the Federal Council of Medicine. In the results and discussion, three subtitles are presented exploring the theme. In the first subtitle, the constitutional principles that are related to the directives are delimited, highlighting the importance of the principles in their implementation. In the second, there is a deepening of the theme of the directives, based on the clarification of related concepts and terms. The third subtitle explores the Brazilian legal system around the advance directives of will and a discussion is woven about the need for a specific regulatory law, describing important legal instruments compatible with the directives. It was evaluated that the directives find legal support in the Federal Constitution and in other provisions of the Brazilian legal system, however, the absence of a specific law limits their use. Thus, it is concluded that the discussion in this sense needs to advance and that the approval of a law that would discipline the advance directives of will would be a gain for society.